Compensated convexity methods for approximations and interpolations of sampled functions in Euclidean spaces: applications to contour lines, sparse data and inpainting - Zhang, Kewei; Crooks, Elaine; Orlando, Antonio (Society for Industrial and Applied Mathematics, 2018)
This paper is concerned with applications of the theory of approximation and interpolation based on compensated convex transforms developed in [55]. We apply our methods to (i) surface reconstruction starting from the knowledge of finitely many level sets (or ‘contour lines’); (ii) scattered data approximation; (iii) image inpainting. For (i) and (ii) our methods give interpolations. For the case of finite sets (scattered data), in particular, our approximations provide a natural triangulation and piecewise affine interpolation. Prototype examples of explicitly calculated approximations and inpainting results are presented for both finite and compact sets. We also show numerical experiments for applications of our methods to high density salt & pepper noise reduction in image processing, for image inpainting and for approximation and interpolations of continuous functions sampled on finitely many level sets and on scattered points.